Nutrient Inputs Alleviate Negative Effects of Early and Subsequent Flooding on Growth of Polygonum hydropiper With the Aid of Adventitious Roots - Chen, Yu-Han; Wei, Guan-Wen; Cui, Yuan; Luo, Fang-Li (Frontiers in Plant Science, 2022)
Riparian plants are exposed to harmful stress induced by flooding, which is often accompanied by eutrophication in the Three Gorges Region. The phenomenon is mainly caused by domestic sewage discharges, slow water flow, and agricultural fertilizer pollution. Simulating abiotic stress, such as flooding at the initial period, can act as a signal and induce positive responses of plants to subsequent severe stress. In addition, eutrophication supplies nutrients, provides a favorable environment in the early stages of plant, and facilitates good performance in later development. However, whether early flooding (with or without eutrophication) acts as positive cue or as stress on plants at different developmental stages remains unclear. To address this question, seeds of Polygonum hydropiper were collected from low and high elevations in the hydro-fluctuation belt of the Three Gorges Reservoir Region. Plants germinated from these seeds were subjected to shallower and shorter early flooding treatments with or without eutrophication. Subsequently, plants were subjected to deeper and longer flooding treatments with or without eutrophication. Early flooding and eutrophic flooding significantly induced generation of adventitious roots, suggesting morphological adaptation to flooding. Although early flooding and eutrophic flooding treatments did not increase plant biomass in subsequent treatments compared with control, stem length, length and width of the 1st fully expanded leaf, and biomass of plants in the early eutrophic treatment were higher than these of the early flooding treatment plants. These results suggest a negative lag-effect of early flooding, and also indicate that nutrient inputs can alleviate such effects. Similarly, subsequent eutrophic flooding also enhanced plant growth compared with subsequent flooding, showing significantly higher values of leaf traits and adventitious root number. Plants originated from low elevation had significantly higher functional leaf length and stem biomass compared with those from high elevation. These results suggest that nutrient inputs can alleviate negative effects of early and subsequent flooding on growth of P. hydropiper with the generation of adventitious roots.